2017
DOI: 10.1371/journal.pone.0172138
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and apoptosis induction in human thyroid carcinoma cells exposed to the essential oil from Pistacia lentiscus aerial parts

Abstract: BackgroundEssential oils from the aerial parts (leaves, twigs and berries) of Pistacia lentiscus (PLEO) have been well characterized for their antibacterial and anti-inflammatory properties; however, poor information exists on their potential anticancer activity.MethodsIncreasing concentrations of PLEO (0.01–0.1% v/v, 80–800 μg/ml) were administered to a wide variety of cultured cancer cells from breast, cervix, colon, liver, lung, prostate, and thyroid carcinomas. Fibroblasts were also included as healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…Of note, mGPDH-rich FTC133 cells are characterized by a significantly higher proliferation rate (doubling time 27h) compared to BCPAP cells (doubling time 30-36h) (13,20). …”
Section: Resultsmentioning
confidence: 99%
“…Of note, mGPDH-rich FTC133 cells are characterized by a significantly higher proliferation rate (doubling time 27h) compared to BCPAP cells (doubling time 30-36h) (13,20). …”
Section: Resultsmentioning
confidence: 99%
“…Several reports have shown that the anti-proliferative activities of different essential oils towards various cancer cells are mediated by apoptosis [30-32]. To determine whether the cytotoxic effects of F-PSEO and L-PSEO are associated with induction of apoptosis, MCF-7 and MDA-MB-231 cells were treated with increasing concentrations of either oil and then analyzed by flow cytometry after staining with FITC-an-nexin-V/7-AAD.…”
Section: Resultsmentioning
confidence: 99%
“…However, antitumor activity of all mastic extracts is much lower than that of anticancer drugs (TS=4-2,961) (25). It has recently been reported that the cytotoxic effect of antineoplastic drugs (cisplatin, 5-fluorouracil and etoposide) against FTC-133 thyroid cancer cells was enhanced by essential oils from the aerial parts (leaves, twigs and berries) of Pistacia lentiscus (1). It, thus, remains to be investigated whether ethyl acetate extract of mastic and antitumor agents show such synergistic effect in the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its unique shape and diverse efficacy, mastic has been called "the tear drop of Christ". Mastic extracts have been reported to show antitumor activity (including the enhancement of anticancer drugs' action and induction of apoptosis via oxidative stress) (1,2), antioxidant activity (that correlated with phenolic and flavonoid contents) (3)(4)(5)(6)(7)(8), antibacterial activity (9)(10)(11), modulating activity of drug-metabolizing enzymes (12,13) and antiviral activity (14)(15)(16)(17). However, most previous investigators did not describe the chemotherapeutic index of these activities (that is the ratio of the biological activity to cytoxicity), even though there is a cautionary note that mastic extracts showed potent cytotoxicity (18).…”
mentioning
confidence: 99%